PLASTIKNOLOGY DEVELOPMENT AND UTILIZATION AMONG PERSON WITH DISABILITY (PWDs) IN SINACABAN, MISAMIS OCCIDENTAL - Liberty B., Doncillo Ma.; Sofia C., Naelga (International Journal of Research -GRANTHAALAYAH, 2018)
In response to the global community problem on solid waste management and the empowerment of the persons with disability (PWDs), this study is focused on Plastiknology development and utilization among persons with disability (PWDs) in Sinacaban, Misamis Occidental, Philippines. The study employed IPO (input process output) model using the respondents’ profile as the input variables and sanitation, sorting, cutting, folding and connecting skills as the process variables. Plastiknology products such as coin purse, clutch bag, wallet and placemats serves as the output variables. Using descriptive statistics, the mean, standard deviation, frequency, percentage and percentage distribution are used to describe each variable. Regression analysis was used to test the input and process variables’ influence on the creation of the output products. Statistics shows minimal background on handicrafts, but interest in trainings is high. Active participation on livelihood trainings was shown in respondents’ positive attendance, attitude and product construction. As a result, there was no significant difference between self-evaluated and post-evaluated skills. Qualitatively, the products of the partcipants are promising and well-constructed. It was therefore recommended that the national and local institutions shall provide livelihood assistance to special sectors such as PWDs by facilitating the continuity of this livelihood program.